منتخب شروح سنن نسائی کا تعارف اور منہج و اسلوب : Introduction of Selected Sharḥ Sunan al-Nasāʼī and their Style - Dr Muhammad Waris Ali; Muhammad Irfan (MEI, 2024)
Sunan al-Nasāʼī is the famous book of Hadith that is counted in the Books of Siha Sitta. Imam al-Nasāʼī compiled this book with the determination that there should be no Ḍaʻīf Hadith in it. That is why there are a few Ḍaʻīf.Hadiths in this book. He was also very committed to the practice of the correct word of Hadith. This book has been explained by different scholars in Arabic and urdu languages but this research article focuses to the selected two sharuh of Sunan al-Nasāʼi that are written in Urdu language. 1st Sunan al-Nasāʼī by Muhammad Liaqat Ridhwi and second Motarjam Sunan al-Nasāʼī by Hafiz Muhammad Amin. Both sharuh have been written in brief and to the point. Volumes of sharah Sunan Nisai six but Sharḥ Sunan al-Nasāʼī by Hafiz Muhammad Amin is in seven volumes. harah Sunan al-Nasāʼī by Hafiz Muhammad Amin was published in 2011 and the Sharḥ Sunan al-Nasāʼī by Liaqat Rizwi in 2015 by Shabir Brothers. Keywords: Sunan al-Nasāʼī, Imam Nisai, Sharuh, Sharḥ Sunan al-Nasāʼī, Liaqat Rizwi, Hafiz Amin